Edukasi Pertolongan Pertama Kegawatdaruratan pada Gigitan Ular - Munawaroh, Intan; Audilla, Amita; Yuli Astuti , Wiwid; Anggraini, Ria; Ady Erwansyah, Rio; Arief Hidayat, Shulhan; Dwi Prasetio, Ossi (ABHIPRAYA: Jurnal Pengabdian Masyarakat Kesehatan dan Sains, 2024)
Snake bites are a health problem that is often experienced by people. Improper handling of snake bites can result in death. This is caused by damage to body tissue, swelling, decreased blood pressure, corneal damage, uveal bleeding, and rupture of erythrocytes. The aim of this Community Service is to provide knowledge to people in the gymnastics community about first aid for snake bites in Campurdarat District. Community service activities are carried out through several stages, namely the planning, implementation and evaluation stages. At the planning stage, the target audience is determined. The implementation phase provides a pretest questionnaire before providing education, then continues with providing material for 60 minutes to the gymnastics community and continues with a question and answer session. The Evaluation Stage is providing a posttest questionnaire. The result was that before being given education about snakebite emergency first aid, almost 9 people (23%) had good knowledge, half of those given education were 20 people (50%) who had good knowledge. In the upcoming Community Service activities, it is hoped that first aid simulations for snakebite emergencies will be provided.